IMPLEMENTASI CSR PT. LCI DALAM PEMBERDAYAAN MASYARAKAT LHOKNGA-LEUPUNG DALAM TINJAUAN MAṢLAḤAH - Eka Nurlina; Rusdi Rusdi (universitas teuku umar, 2020)
Corporate Social Responsibility (CSR) is the corporate social responsibility towards the environment and the communities where the company runs its business activities. CSR activities was undertaken to realize the benefit for the community, not only to meet legal obligations but also to be able to provide the value of empowerment or improving quality of life. This review article about Implementation Corporate Social Responsibility (CSR) PT. Lafarge Cement Indonesia in Community Empowerment Lhoknga-Leupung in Reviews Maṣlaḥah. The results showed that PT. LCI has been conducting CSR activities in several programs namely education programs, economic development, socio-religious and health sector. As for the conformity with the concept Maṣlaḥah, researchers use the modification of the CSR pyramid Carrol and the Pyramid Maṣlaḥah. When viewed in terms of the program and achievement objectives are appropriate, but not yet in accordance with the concept Maṣlaḥah, by advancing the Al-Ḍharuriyyah, then continued with al-Ḥajjiyyah and lastly is Al-Tahṣiniyyah. Similarly, if assessed in terms of the implementation of the program, there are still problems such as less targeted, lack of transparency in the reporting of CSR programs and there is an element of RIBA in the development of economic expansion.Corporate Social Responsibility (CSR) is the corporate social responsibility of the environment and the community where the company conducts its business activities. PT. LCI as a foreign company that conducts business activities in ACEH precisely in Lhoknga has been running CSR activities since the year 2009. CSR activities are done to create the benefits for the community, not only to fulfill the legal obligation, but with the CSR program is able to provide the value of empowerment or improvement of the quality of life of society. This article is about the implementation of corporate social responsibility (CSR) PT. Lafarge Cement Indonesia in empowering the community Lhoknga-Leupung in the review Maṣlaḥah.Keywords: CSR, Community Empowerment, Maṣlaḥah, PT. LCI